Evaluation of the molecular mechanisms associated with cytotoxicity and inflammation after pulmonary exposure to different metal-rich welding particles. Issue 6 (3rd July 2017) - Shoeb, Mohammad; Kodali, Vamsi; Farris, Breanne; Bishop, Lindsey M.; Meighan, Terence; Salmen, Rebecca; Eye, Tracy; Roberts, Jenny R.; Zeidler-Erdely, Patti; Erdely, Aaron; Antonini, James M.
Abstract: Welding generates a complex aerosol of incidental nanoparticles and cytotoxic metals, such as chromium (Cr), manganese (Mn), nickel (Ni), and iron (Fe). The goal was to use both in vivo and in vitro methodologies to determine the mechanisms by which different welding fumes may damage the lungs. Sprague-Dawley rats were treated by intratracheal instillation (ITI) with 2.0 mg of gas metal arc-mild steel (GMA-MS) or manual metal arc-stainless steel (MMA-SS) fumes or saline (vehicle control). At 1, 3, and 10 days, bronchoalveolar lavage (BAL) was performed to measure lung toxicity. To assess molecular mechanisms of cytotoxicity, RAW264.7 cells were exposed to both welding fumes for 24 h (0–100 μg/ml). Fume composition was different: MMA-SS (41% Fe, 29% Cr, 17% Mn, 3% Ni) versus GMA-MS (85% Fe, 14% Mn). BAL indicators of lung injury and inflammation were increased by MMA-SS at all time points and by GMA-MS at 3 and 10 days after exposure. RAW264.7 cells exposed to MMA-SS had elevated generation of reactive oxygen species (ROS), protein-HNE (P-HNE) adduct formation, activation of ERK1/2, and expression of cyclooxygenase-2 (COX-2) compared to GMA-MS and control. Increased generation of ROS due to MMA-SS exposure was confirmed by increased expression of Nrf2 and heme oxygenase-1 (HO-1). Results of in vitro studies provide evidence that stainless steel welding fume mediate inflammatory responses via activation of ROS/P-HNE/ERK1/2/Nrf2 signaling pathways. These findings were corroborated by elevated expression of COX-2, Nrf2, and HO-1 in homogenized lung tissue collected 1 day after in vivo exposure.